2023
DOI: 10.1038/s41598-023-38653-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optimization-based method for the generation of patient-specific models of Purkinje networks

Abstract: Cardiac Purkinje networks are a fundamental part of the conduction system and are known to initiate a variety of cardiac arrhythmias. However, patient-specific modeling of Purkinje networks remains a challenge due to their high morphological complexity. This work presents a novel method based on optimization principles for the generation of Purkinje networks that combines geometric and activation accuracy in branch size, bifurcation angles, and Purkinje-ventricular-junction activation times. Three biventricula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Ventricular fibre orientation was incorporated using the rule-based method by (Doste et al, 2019) following anatomical observations from (Streeter et al, 1970). The anatomical description of the Purkinje network was incorporated using the algorithm by (Berg et al, 2023; Camps et al, 2023) to achieve consistency between simulated and clinical QRS complexes, as shown in Figure 4A. CV in fibre, sheet and normal directions were 65, (Taggart et al, 2000), 38 and 47 cm/s (see supplementary Figure S9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ventricular fibre orientation was incorporated using the rule-based method by (Doste et al, 2019) following anatomical observations from (Streeter et al, 1970). The anatomical description of the Purkinje network was incorporated using the algorithm by (Berg et al, 2023; Camps et al, 2023) to achieve consistency between simulated and clinical QRS complexes, as shown in Figure 4A. CV in fibre, sheet and normal directions were 65, (Taggart et al, 2000), 38 and 47 cm/s (see supplementary Figure S9).…”
Section: Methodsmentioning
confidence: 99%
“…A) Patient heart and torso geometries with electrode locations (Mincholé et al, 2019) were combined with a personalised Purkinje conduction network to reproduce the patient’s ECG as in (Berg et al, 2023; Camps et al, 2023). B) Small, medium and large scar created using (Cardone-Noott et al, 2014; Hill et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation